Analisis Peraturan Pemerintah Nomor 101 Tahun 2014 Terhadap Bahan Berbahaya Dan Beracun di Kota Batam - Ukas Ukas; Zuhdi Arman (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2020)
Environment is very important in the human life cycle. In modern times problems arise regarding the environment. In this paper the issue raised is the impact of environmental pollution caused by sewage and waste as well as the government's efforts to prevent environmental pollution.To these problems occurs line with technological developments who without pay attention to environment. Environmental pollution has an impact on health, aesthetics, economic losses, and disruption of natural ecosystems. The method used in this paper is a juridical-empirical, theoretical approach using facts and laws. The conclusion of these problems is the lack of awareness on the part of industry employers and the community to protect the environment from pollution and waste bins will berdampaknya the destruction of natural ecosystems and reduced environmental quality standards.